2006
DOI: 10.1128/jb.00004-06
|View full text |Cite
|
Sign up to set email alerts
|

RcsF Is an Outer Membrane Lipoprotein Involved in the RcsCDB Phosphorelay Signaling Pathway in Escherichia coli

Abstract: The RcsCDB signal transduction system is an atypical His-Asp phosphorelay conserved in ␥-proteobacteria. Besides the three proteins directly involved in the phosphorelay, two proteins modulate the activity of the system. One is RcsA, which can stimulate the activity of the response regulator RcsB independently of the phosphorelay to regulate a subset of RcsB targets. The other is RcsF, a putative outer membrane lipoprotein mediating the signaling to the sensor RcsC. How RcsF transduces the signal to RcsC is un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
102
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 42 publications
3
102
0
Order By: Relevance
“…However, it was later demonstrated that the Rcs activation by RcsF overproduction is dependent on RcsC (Majdalani et al, 2002;Hagiwara et al, 2003) and that RcsF is an outermembrane lipoprotein (Castanié-Cornet et al, 2006). A variety of environmental and mutational stresses require RcsF to stimulate Rcs signalling , and RcsF is now regarded as an inherent component of the Rcs system with a crucial role in transmitting the signal to RcsC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was later demonstrated that the Rcs activation by RcsF overproduction is dependent on RcsC (Majdalani et al, 2002;Hagiwara et al, 2003) and that RcsF is an outermembrane lipoprotein (Castanié-Cornet et al, 2006). A variety of environmental and mutational stresses require RcsF to stimulate Rcs signalling , and RcsF is now regarded as an inherent component of the Rcs system with a crucial role in transmitting the signal to RcsC.…”
Section: Introductionmentioning
confidence: 99%
“…Asp at position 2 functions as an inner-membrane retention signal (Tokuda & Matsuyama, 2004). RcsF has Ser at position 2 and is transported to the outer membrane (Castanié-Cornet et al, 2006). An E. coli pgsA null mutant defective in phosphatidylglycerophosphate synthase and completely lacking the major acidic phospholipids, phosphatidylglycerol and cardiolipin, is viable, if it also lacks the major outer-membrane lipoprotein encoded by the lpp gene, but shows a thermosensitive growth defect at 42 u C (Kikuchi et al, 2000;Matsumoto, 2001;Suzuki et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, it lacks significant homology to other proteins and does not contain any predicted active sites or conserved domains. Membrane proteins are key players in allowing 2-component systems to recognize their cognate signals and communicate with other 2-component systems (19,20). In this study we elucidated the role of YfhG (QseG) in pedestal formation and further characterized the QseEF system and its roles in responding to environmental signals and regulation of AE lesion formation.…”
mentioning
confidence: 99%
“…The Rcs system is activated by alterations of the envelope (for reviews see Majdalani & Gottesman, 2005;Francez-Charlot et al, 2005a). Most of the signalling to RcsC is mediated by the outer membrane lipoprotein RcsF with a few exceptions such as the overproduction of the membrane-associated chaperone-like protein DjlA (Castanié-Cornet et al, 2006). RcsB can be activated independently of the RcsFCD phosphorelay by interacting with an accessory cofactor, RcsA.…”
Section: Introductionmentioning
confidence: 99%